The construction of the referent The place where I live in opinion articles: a dialogue between referential theory and objectivity in brackets - Filipe Fontenele Oliveira; Maria Helenice Araújo Costa (Entrepalavras: Revista de Linguística do Departamento de Letras Vernáculas da Universidade Federal do Ceará, 2016)
This paper aims to propose a discussion about the construction of the referent The place where I live in the V edition of the Portuguese Language Olympiad Writing the Future, while trying to hold a dialogue between the theory of referentiation and the concept of objectivity in brackets proposed by biologist Humberto Maturana. Part of this discussion includes the partial results of our master's research in the Postgraduate in Applied Linguistics Program, State University of Ceará. In this research, we analyze nine texts of opinion written by students of a state school in Fortaleza, produced and intended for this educational event. However, for the current work, we analyze just one text. We seek to achieve the approximation of the theories under discussion in the production of the texts, including the reference articulation that cover The place where I live in the analyzed text. From what we see, the construction of this reference exceeds relations between the words marked by direct expressions or predications attached to it. In fact, it occurs in relation to other related available in text and occurs before the mention by linguistic expressions, as already part of individual and collective buildings, marked by sociohistoric aspects and the intertextual relations with other sources.